1984
DOI: 10.4315/0362-028x-47.6.453
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Chemical Changes of Spotted Shrimp (Pandalus platyceros) Stored Under Modified Atmospheres

Abstract: Shrimp (Pandalus platyceros) were packed head-on and head-off in pouches with air or 50 or 100% CO2 and stored at 0 to 2°C for up to 23 d. Carbon dioxide in modified atmosphere pouches dissolved in the liquid phase and the pH decreased. As storage progressed, the pH increased. Only 100% CO2 was effective in extending the lag in bacterial growth, but the greatest weight or drip was also obtained with this atmosphere. The bacterial flora changed from mixed gram-negative and gram-positive organisms to a predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 7 publications
8
22
2
Order By: Relevance
“…After an initial drop in CO 2, the level stabilized to between 42 and 47%. This is in contrast to increases in CO 2 levels after storage reported by Layrisse and Matches (1984). Under identical conditions to the current study, Lannelongue et al (1982) also found only a slight increase in CO 2 after storage of packed shrimp.…”
Section: Headspace Analysiscontrasting
confidence: 55%
See 2 more Smart Citations
“…After an initial drop in CO 2, the level stabilized to between 42 and 47%. This is in contrast to increases in CO 2 levels after storage reported by Layrisse and Matches (1984). Under identical conditions to the current study, Lannelongue et al (1982) also found only a slight increase in CO 2 after storage of packed shrimp.…”
Section: Headspace Analysiscontrasting
confidence: 55%
“…Layrisse and Matches (1984) obtained higher drip loss from Pandalus platyceros after using similar postharvest and MAP storage conditions as the current study. Table 2 shows the mean scores recorded for the two species of raw prawns for three trials stored in MAP at 4…”
Section: Drip Loss Within Prawn Packs At Openingmentioning
confidence: 49%
See 1 more Smart Citation
“…The initial PV values (0 day) for the control and nisin-treated fish averaged 0.053 and 0.046 (meq O 2 /kg muscle), respectively. At this stage, which is named as slow oxidation period, some intracellular energy sources such as ATP offering electrons whereby presenting antioxidative properties and as soon as these energy sources are consumed, slow oxidation period ends up followed by a rapid increase in peroxide level (Layrisse and Matches 1984). Min et al (2008) compared the susceptibility of meats from different animal species to lipid oxidation during storage at 4°C.…”
Section: Lipid Oxidation Indicesmentioning
confidence: 99%
“…In order to extend the shelf-life of shrimp, many methods of packaging have been investigated to control the changes of sensory attributes and the proliferation of spoilage bacteria in raw shrimp, such as air packaging (AP), aerobic polyvinylchloride packaging (Chen and Xiong, 2008), vacuum packaging (VP), modified atmosphere packaging (Layrisse and Matches, 1984;Matches and Layrisse, 1985;Lu, 2009), especially modified atmosphere packaging (MAP), as one of the most effective applications for shelf-life extension of seafood, is becoming increasingly popular.…”
Section: Introductionmentioning
confidence: 99%